The Impact of Operational Stressors Among Police Officers in Managing Anti-Illegal Drugs Operation in Masbate Police Provincial Office - Quinito, Reymond (JPAIR Multidisciplinary Research, 2026)
This study examines the impact of operational stressors on police officers engaged in anti-illegal drug operations, highlighting the importance of promoting well-being and effective law enforcement aligned with global and national security goals. Despite extensive global research on police stress, limited localized studies in the Philippine context—particularly at the provincial level—create a gap in understanding how operational stressors specifically affect officers in anti-illegal drug operations, thereby establishing the originality of this study. It aims to determine the profile of police officers, identify common operational stressors, describe their patterns and levels, assess their impact on performance and well-being, and propose a stress management program. The study utilized a quantitative research design employing a descriptive approach, with respondents drawn from police officers of the Masbate Police Provincial Office through total enumeration sampling; data were collected using a validated self-constructed structured questionnaire administered through an online platform, and analyzed using statistical tools such as frequency, percentage, ranking, and weighted mean. Findings revealed that police officers experience significant stress from operational demands, workload, organizational factors, and public perception, which commonly occur and exert varying levels of impact on decision-making, job satisfaction, mental and physical health, interpersonal relationships, and community engagement, as reflected in the frequency, ranking, and weighted mean results across identified variables. Based on these results, the study concludes that operational stressors substantially influence police performance and well-being, thereby necessitating the implementation of a Comprehensive Stress Management and Wellness Program to enhance resilience, improve job performance, and support the overall welfare of police personnel.
Keywords: Impact; Operational Stressors; Police Officers; Illegal Drug Operations; Descriptive Quantitative; Philippines